SP1.2.1 The Theatre Training Checklist (TTC): A toolkit to improve training within the operating theatre. (9th August 2022) - Aldoori, Joanna; Peter, Mark; O'Regan, David; Robson, Andrew
Abstract: Aims: The operating theatre is a crucial learning environment for different trainees (nurses, anaesthetists, surgeons etc.) Equity of access is essential to achieve their individual training requirements. Traditionally, opportunities within a theatre list are informally discussed between trainers and trainees at some point during the list. Furthermore, there is currently limited discussion between different members of the full team. The Theatre Training Checklist (TTC) is a simple framework that aims to facilitate coordination of training for all team members. Methods: The TTC was devised as an extension of the WHO checklist. It consists of four stages: Trainer/Trainee discussion before theatre brief regarding training goals for the list, formal identification of all trainees within the theatre brief, explanation to the team of what each trainee will undertake, followed by use of theatre debrief to reprise whether training goals were met. The TTC was piloted and outcomes measured using an anonymised structured questionnaire from across the entire team. Results: 27 staff participated, including 7 trainees. Individuals' understanding of trainees' objectives improved as a result of the TTC (25/27, 92.6%) along with perceived improved theatre list efficiency (18/27, 66.6%). All trainees agreed that the checklist improved achievement of their training objectives. Qualitative feedback included: " This is a great way to identify what students and trainees want to achieve in theatre and how we can work together to overcome any difficulties " Conclusion: Initial data suggests the checklist qualitatively improves training. The TTC Toolkit is available for use and consists of the checklist tool and an instructional video.